Knowledge and Attitude to Quality of Life Elderly Complete Denture in New Normal - Fadriyanti, Okmes; Afriza, Dhona; Salsabila, Qonitah (Dentistry Faculty, 2024)
Background: Knowledge and attitudes of the community, especially older people who wear complete dentures, can influence the quality of life. Quality of life in older people with tooth loss can be treated by making dentures, which are generally complete dentures. Objective: This study determined the relationship between knowledge and attitudes towards the quality of life of elderly complete denture users during the new normal period. This type of research is an analytical survey. Methods: The research method is analytic survey research using a cross-sectional design. The research sample used a purposive sampling technique with a sample size of elderly patients using complete dentures, totaling 36 respondents at the Baiturrahmah General Hospital during the new normal period in January-December 2022. Univariate data analysis processing was presented as a frequency distribution and bivariate data analysis using the Spearman correlation test. Results: Significant (p0.05) in the good knowledge category for 20 (55.6%) respondents, positive attitude category for 27 (75%) respondents, and high quality of life category for 18 (50%) respondents. Conclusion: Knowledge of Quality of life 0.01 (p0.05) and attitudes towards quality of life 0.05 (p0.05).